Allelopathy and allelopathic substances of mango (Mangifera indica L.). Issue 4 (28th December 2020) - Kato‐Noguchi, Hisashi; Kurniadie, Denny
Abstract: Homegarden, traditional agroforestry system in tropical and subtropical regions, sustains the availability of daily necessities. Mango ( Mangifera indica L.) is an essential tree in the homegardens and is used for multiple purposes such as food, folk medicine, fuel, timber, and apiculture. The interaction between mango and weeds or crops has been evaluated in terms of allelopathy and the evidence of the allelopathy accumulated in the literature over two decades. The leaf extracts and leachate of mango inhibited the germination and growth of several other plants species. Soil collected from mango orchard shows growth inhibitory activity. Residues of mango leaves also suppressed the growth of other plant species. Phytotoxic substances such as coumaric, vanillic, caffeic, cinnamic, gallic and protocatechuic acids, and methyl gallate and quercetin‐3‐ O ‐α‐glucopyranosyl‐(1 → 2)‐β‐D‐glucopyranoside were identified in mango leaves. Those compounds may be released into the soil through the leaf leachate and the decomposition of plant residues and they can inhibit the germination and the growth of neighboring plants as allelopathic substances. Therefore, the allelopathy of mango is potentially useful for the weed management options in homegardens and other agriculture settings to reduce commercial herbicide dependency.